Tinjauan Hukum terhadap Dampak Kecanduan TikTok terhadap Kesehatan Mental Remaja: Studi Kasus di Kalangan Pelajar - Nisa’, Ihda Shofiyatun; Ni’mah, Lailatun; Nurroiffah, Ainin Ainiyya (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
This research aims to analyze the impact of TikTok addiction on the mental health of teenagers, especially among students, as well as reviewing laws related to protecting their mental health. TikTok, as a social media platform that is very popular among teenagers, has the potential to influence users' psychological conditions, both positively and negatively. Addiction to these platforms can cause mental disorders such as anxiety, depression, stress, and sleep disorders. In addition, excessive TikTok users can affect teenagers' social interactions and cognitive development. This research also examines how the legal system in Indonesia, including regulations regarding the protection of children and adolescents, seeks to provide protection against the negative impacts of social media use, as well as limitations in dealing with the phenomenon of TikTok addiction. The results of this research show that even though there are regulations governing the protection of children in cyberspace, more comprehensive policies are still needed regarding monitoring the use of social media, education regarding its negative impacts, and protecting the mental health of teenagers. This research suggests the need for collaboration between the government, educational institutions, and families to create policies that can reduce the negative impact of social media on adolescent mental health.